Enhancing People-to-People Cooperation between ASEAN and East Asia Countries through Counterparts: The Case of Indonesian Student in Taiwan - Paramitaningrum, Paramitaningrum (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2013)
Besides businessmen and workers, Indonesian students have become one of the recent important actors in Indonesia - Taiwan bilateral relations. Currently, Taiwan became one of the popular destinations among Indonesians to pursue their highest degree. In 2013, the numbers of Indonesian students has reached 3000 persons, made them the third largest group of Southeast Asian students in Taiwan after Vietnamese and Malaysians. The Indonesian students are quite organized and active. Giving the lack of diplomatic relations between both countries, these students are potential to be one of the significant actors to bridge Indonesia - Taiwan relations. However, they have some limitations on conducting their activities. On the Taiwan side, this trend has not gained sufficient responds. Indonesia is still considered an unattractive object to study, comparing to other Southeast Asian countries. Therefore interaction tends to be one side only. This paper would discuss on (1) what the Indonesian students in Taiwan can do to maximize their capabilities to attract Taiwanese to learn more about Indonesia; (2) How the Taiwanese should respond to these trends, in order to create two ways of interaction. In that case, the counterparts are significant to bridge the limitations of mutual interaction between both states, especially to eliminate the unclear perceptions among Taiwanese to Indonesia, which might affect Indonesia – Taiwan bilateral relations, and to promote Indonesia in the better outlook.